Intravoxel Incoherent Motion Diffusion-weighted MR Imaging of the Liver: Effect of Triggering Methods on Regional Variability and Measurement Repeatability of Quantitative Parameters - Lee, Yedaun; Lee, Seung Soo; Kim, Namkug; Kim, Eunki; Kim, Yeong Jae; Yun, Sung-Cheol; Kühn, Bernd; Kim, In Seong; Park, Seong Ho; Kim, So Yeon; Lee, Moon-Gyu (Radiology, 2015)
To compare the influence of triggering methods for diffusion-weighted imaging (DWI) on apparent diffusion coefficient (ADC) and intravoxel incoherent motion (IVIM) parameters in the liver, as well as regional variability and measurement repeatability. In this institutional review board-approved prospective study, 12 healthy volunteers (six women, six men; mean age, 30 years) underwent 1.5-T DWI of the liver by using nine b values twice with free breathing (FB) without triggering (mean acquisition time ± standard deviation, 3.7 minutes ± 0), respiratory triggering (RT) (mean acquisition time, 6.8 minutes ± 1.4), and echocardiography triggering (ET) (mean acquisition time, 8.3 minutes ± 2.0) after providing written informed consent. ADC and IVIM parameters, including pure diffusion coefficient (D), perfusion fraction (f), and perfusion-related diffusion coefficient (D*), were measured by using 15 regions of interest (ROIs). Regional variability of ADC and IVIM parameters and measurement repeatability were evaluated by using the coefficient of variation (CV) across ROIs and within-subject CV, respectively. ET DWI (range of CV across ROIs, 6.69%-20.0%) resulted in significantly decreased regional variability of ADC, D, and f, compared with FB DWI (13.86%-35.8%) and RT DWI (15.15%-35.91%, P ≤. 049). ET DWI showed better repeatability of ADC measurement (within-subject CV range, 3.17%-4.12% for ET DWI; 4.15%-4.74% for FB DWI; and 2.33%-6.96% for RT DWI), D (4.05%-5.34% for ET DWI, 4.11%-12.51% for FB DWI, and 3.19%-16.17% for RT DWI), and f (7.6%-9.86% for ET DWI, 13.83%-16.81% for FB DWI, and 10.05%-12.10% for RT DWI), compared with FB DWI and RT DWI, with significant differences in within-subject CV for D in the left hepatic lobe compared with RT DWI (P = .023) and for f compared with FB DWI (P ≤ .032). For all three imaging techniques, D* showed the worst repeatability (within-subject CV, 57.05%-156.61%) among ADC and IVIM parameters. ET DWI is more effective for decreasing regional variability of ADC and IVIM parameters than FB DWI or RT DWI; it may improve measurement repeatability by reducing cardiac motion-induced measurement error.